LEVERAGING DIGITAL INNOVATION FOR SUSTAINABLE PROCUREMENT PERFORMANCE: A CASE STUDY OF SOUTH SUMATRA’S PROCUREMENT OFFICE - Tatan Mayandripan; Endi Rekarti (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2025)
This study aims to analyze innovative management practices in digital procurement and evaluate their impact on efficiency and transparency at the South Sumatra Provincial Goods and Services Procurement Office. This study used a qualitative approach with semi-structured interviews with 9 participants consisting of functional officials and procurement staff. Data were analyzed thematically through an interpretative approach. The results showed that innovative management is understood as an effort to simplify the process through system integration (SPSE, e-Catalog, e-Contract), document digitization, and strengthening internal coordination. The implementation of digital procurement is proven to increase time and cost efficiency, and strengthen transparency through public access to procurement information. However, challenges still exist in the form of limited technological infrastructure, human resource readiness, and limited system features. The study concludes that the success of digital procurement depends on adaptive managerial innovation and adequate institutional support. Strategic recommendations include increasing human resource capacity, strengthening digital infrastructure, improving system features, and cross-agency collaboration as an effort to realize efficient, transparent, and sustainable public procurement.